Inhibition of Adult Hippocampal Neurogenesis Plays a Role in Sevoflurane-Induced Cognitive Impairment in Aged Mice Through Brain-Derived Neurotrophic Factor/Tyrosine Receptor Kinase B and Neurotrophin-3/Tropomyosin Receptor Kinase C Pathways - Xu, Lichi; Guo, Yanjing; Wang, Gongming; Sun, Guoqing; Sun, Wei; Li, Jingjing; Li, Xinlei; Wu, Jiangnan; Zhang, Mengyuan (Frontiers in Aging Neuroscience, 2022)
Sevoflurane anesthesia induces cognitive impairment, which may lead to perioperative neurocognitive disorders. However, the factors and molecular mechanism underlying this impairment remains unclear. Adult hippocampal neurogenesis (AHN) in the subgranular zone of the hippocampus has been implicated in cognitive processes. Nonetheless, the direct role of AHN in sevoflurane-induced cognitive impairment has never been demonstrated. In this study, we explored the age and the concentration factors and the role of AHN inhibition in sevoflurane-induced cognitive impairment in sevoflurane inhalation model mice. We found that 3% sevoflurane exposure induced significant cognitive impairment and inhibition of AHN in aged mice but not adult mice. Expression of BDNF/TrkB and NT-3/TrkC was also decreased by 3% sevoflurane exposure in aged mice. Hippocampal BDNF or NT-3 microinjection could partially improve the sevoflurane-induced cognitive impairment and AHN inhibition, respectively. These results demonstrate that the cognitive impairment caused by sevoflurane inhalation is related to patient age and sevoflurane concentration. In conclusion, the molecular mechanism of cognitive impairment in the elderly is related to the inhibition of AHN through the BDNF/TrkB and NT-3/TrkC pathways. Thus, sevoflurane inhalation anesthesia may be safe for adult patients, but caution should be exercised when administering it to the elderly.